Active Decisions and Pro-social Behavior: A Field Experiment on Blood Donation - Alois Stutzer; Lorenz Goette; Michael Zehnder (University of Basel, Center of Business and Economics (WWZ), 2006)
In this paper, we propose a decision framework where people are individually asked to either actively consent or dissent to some pro-social behavior. We hypothesize that confronting individuals with the choice of engaging in a specific pro-social behavior contributes to the formation of issue-specific altruistic preferences while simultaneously involving a commitment. The hypothesis is tested in a large-scale field experiment on blood donation. We find that this "active-decision" intervention substantially increases the actual donation behavior of people who have not fully formed preferences beforehand.
Keywords: C93; D64; I18; 330; active decision; pro-social behavior; field experiment; blood donation; Altruismus; Test; Soziales Verhalten